On Characterization of Nonuniform Tight Wavelet Frames on Local Fields (Analysis in Theory and Applications, 2018)
In this article, we introduce a notion of nonuniform wavelet frames on localfields of positive characteristic. Furthermore, we gave a complete characterization oftight nonuniform wavelet frames on local fields of positive characteristic via Fouriertransform. Our results also hold for the Cantor dyadic group and the Vilenkin groupsas they are local fields of positive characteristic.